Characterization of actinomycetes antagonistic to Phytophthora fragariae var. rubi, the causal agent of raspberry root rot - Toussaint, V.; Valois, D.; Dodier, M.; Faucher, E.; Déry, C.; Brzezinski, R.; Ruest, L.; Beaulieu, C. (Phytoprotection, 1997)
Eleven actinomycete strains that were previously shown to protect raspberry (Rubus strigosus) plants against Phytophthora infection were characterized. all were shown to belong to the genus Streptomyces. Two strains (EF-34 and EF-76) grew at 4, 15 and 30°C on V8 agar between pHs 5 to 9. Seven strains including EF-34 and EF-76 had both the ability to hydrolyze Phytophthora cell walls and to inhibit Phytophthora growth at 15°C between pHs 5 to 9. all actinomycetes inhibited the growth of P. fragariaevar. rubi and of Pythium ultimum. The growth of other fungal species and of Gram-negative bacteria was inhibited only in the presence of three strains (EF-14, EF-72, and EF-76). The eleven antagonistic actinomycetes were classified into four groups with regard to their resistance to various pesticides used to protect raspberry crops. Strain EF-76 was further characterized. This strain was identified as Streptomyceshygroscopicus var. geldanus, and it was shown to produce geldanamycin, a known antibiotic.